15.3: Roll‐to‐Roll Fine Copper Circuit Patterning Solutions. (28th November 2018) - Chung, Sheng-Hsuan; Lin, Chia-Hui; Hsu, Ming-Ann; Igawa, Akihiko; Hsieh, Tung-Hung
Abstract : Fine copper circuit on flexible substrate is highly demanded components for flexible displays. Two methods have been developed for making high resolution (7um, L/S) circuits with copper thickness up to 10 um: positive‐tone photolithography/wet etching, and semi‐additive photolithography/plating/flash etching processes. High throughput roll‐to‐roll process can be applied using both methods with proprietary positive‐tone photoresists for manufacturing flexible backplane and connector circuits.